The effect of the parameters of sludge age, aeration flow, and hydraulic residence times on the permeability in the membrane bioreactors (Journal of Hama University, 2024)
MBR membrane bioreactors technology has been used for industrial and municipal (domestic) wastewater treatment. This process is based on the integration of the classical or conventional activated sludge (CAS) process with micro membranes filtration processes, in which microorganisms are responsible for the efficient removal of contaminants, while the membranes retain suspended solids, flocs and all What biomass can be reserved in the mixed liquid.This research presents the results of four months (From August to November of 2021) in which the effect of sludge age SRT, aeration rate, and hydraulic retention time on the performance of the bioreactor was studied in terms of permeability, pollutant removal efficiency, and fouling delay. The fouling prediction on the optimal state derived from laboratory experiments was analyzed and studied.mThe sludge age was set as 30 days as the best age applied to the reactor, aeration rate was set as 55 L of air/min as the best permeability aeration condition, and the hydraulic retention time was set: 12.8 hours to raise the efficiency of pollutant removal and delay fouling.
Keywords: MBR): Membrane Bioreactor ) Hydrulic Retention time: HRT MLSS mixed liquor suspended solids Sludge Retention time: SRT